Effects of Intramuscular Midazolam and Lorazepam on Acute Agitation in Non-Elderly Subjects – A Systematic Review - Kousgaard, Sabrina Just; Licht, Rasmus W.; Nielsen, René Ernst (Pharmacopsychiatry, 2017)
Benzodiazepines are commonly used for the treatment of acute agitation in a psychiatric setting.We searched MEDLINE, EMBASE, PsycINFO, and the Cochrane Central Register of Controlled Trials (CENTRAL) for relevant publications. Randomized trials evaluating intramuscular (IM) midazolam or lorazepam given as monotherapy or as add-on treatment, with more than 10 patients aged 18–65 years, conducted in a psychiatric setting, and published between January 1, 1980, and February 3, 2016, were included. 16 studies from a search result of 5 516 studies were included. In total, 577 patients were treated with lorazepam IM 2–4 mg, and 329 patients were treated with midazolam IM 5–15 mg. It is unclear whether lorazepam IM or midazolam IM is as efficacious as an antipsychotic IM. It is a bit more certain that the combination of benzodiazepines IM and a low dose antipsychotic IM is more efficacious than the benzodiazepine and the antipsychotic alone. However, there is no doubt that benzodiazepines are less likely to be associated with treatment emergent side effects, as compared to antipsychotics.
Keywords: agitation; antipsychotics; lorazepam; midazolam